1992
DOI: 10.1128/iai.60.3.791-797.1992
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells mediate protection induced by a Salmonella aroA mutant

Abstract: We have previously shown that an avirulent strain of Salmonella typhimurium, SL3235, blocked in aromatic synthesis, confers high levels of resistance to challenge with virulent Salmonella as early as 3 days postvaccination. In the present studies, it was found that immunization with SL3235 resulted in high levels of natural killer (NK) cell activity in the spleens and peritoneal cavities of C3H/HeJ mice, as measured by cytotoxicity against YAC-1 targets. NK cell activity was at its maximum 2 to 4 days after im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
16
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 22 publications
(36 reference statements)
9
16
0
Order By: Relevance
“…sponses are not involved. Since other bacterial particles such as HK C. parvum, but not 1.1-m latex beads, also induced comparable levels of IFN-␥, these responses might be common with microbial particulate components (30,44). Taken together, the capacities of particles to prime alveolar M in vivo closely parallel the responses of our in vitro cell system.…”
Section: Discussionsupporting
confidence: 59%
“…sponses are not involved. Since other bacterial particles such as HK C. parvum, but not 1.1-m latex beads, also induced comparable levels of IFN-␥, these responses might be common with microbial particulate components (30,44). Taken together, the capacities of particles to prime alveolar M in vivo closely parallel the responses of our in vitro cell system.…”
Section: Discussionsupporting
confidence: 59%
“…During the initial stages of infection, cell wall components of Salmonella such as lipopolysaccharide (LPS) and certain lipoproteins induce a massive inflammatory response in the surrounding tissue, resulting in the expression of inflammatory cytokines [e.g., TNF-␣, interleukin (IL)-1, IL-6, IL-12, and IL-18] and a variety of chemokines that recruit cells of the immune system to these sites [26][27][28][29]. IFN-␥ is also produced during early infection, with natural killer (NK) cells being an important source during this stage [30,31]. Additional potential sources for IFN-␥ are macrophages, B cells, and specialized T cell populations, such as NK T cells, that are able to recognize conserved structural patterns of bacteria [32][33][34].…”
Section: The Immune Response To Salmonellamentioning
confidence: 99%
“…Several studies have demonstrated the importance of the innate immune response in limiting bacterial multiplication and thereby controlling infection, ascribing impor-tant roles for macrophages and natural killer cells in the acute phase of the infection. [50][51][52] Macrophages are the host cells for Salmonella and also initiate the innate immune response to pathogens by producing pro-inflammatory cytokines, such as IL-12 and TNF-a. Interleukin-12 is a known growth factor for natural killer cells, which have the capacity to rapidly secrete IFN-c, a cytokine with a potent macrophage-activating capacity.…”
Section: Discussionmentioning
confidence: 99%